THE STUDY OF FOLK TALES IN 20TH-CENTURY UZBEK FOLKLORE STUDIES - Hamza Kamalovich Allambergenov (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the history of the study of Uzbek folk tales in twentieth-century Uzbek folklore scholarship. It analyzes the major stages in the collection, publication, classification, and scientific investigation of folk tales, highlighting the contributions of prominent Uzbek folklorists. Special attention is paid to the development of theoretical approaches to the study of fairy tales, including their genre classification, genesis, poetics, typology, mythology, symbolic imagery, and artistic structure. The article reviews the scholarly works of Buyuk Karimiy, M. Afzalov, G. Jalolov, G. Jahongirov, K. Imomov, J. Yusupov, M. Jo‘rayev, J. Eshonqulov, and other researchers, demonstrating their role in establishing Uzbek fairy-tale studies as an independent field of folklore research. The study concludes that twentieth-century Uzbek folklore scholarship laid a solid theoretical and methodological foundation for contemporary research on folk tales and significantly contributed to the development of national folklore studies.